Pkm Sosialisasi Peningkatan Protokol Kesehatan dalam Rangka Pencegahan Penyebaran Virus Covid-19 Kepada BKM Masjid Al.Muhajjirin di Desa Paranjulu Sipirok - sagala, nanda suryani; Siregar, Nurelilasari (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
ABSTRACT Introduction: The covid-19pandemic willcontinue for some time to come, so that people inevitably need to adjust to living according to established health protocols to prevent Covid-19 transmission. The aim of the study: to increase BKM knowledge related to preventing the spread of the covid 19-viruspublic. Materials and Methods: Socialization activities for improving helath protocols in order to prevent the spread of the covid-19 virus to the BKM Mosque in Paranjulu Sipirok village with the lecture, discussion and question and answer method. Research Results: BKM managemen of the al-muhajjirin mosque understands helth protocols in preventing the spread of the covid-19 virus Conclusion: BKM administration of al-muhajjirin mosque are able to apply health protocols in the mosque environment